2022
DOI: 10.1155/2022/2314104
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control Analysis of Treatment Strategies of the Dynamics of Cholera

Abstract: A nine-compartment deterministic cholera model was formulated, and the model describes interactions between human, Vibrio cholerae bacteria, and the enviroment that warrant the interaction. Realities and socioeconomic burden influence spread and control mechanism of the disease. The model investigated some effective ways of hindering cholera outbreak and spread. The existence and uniqueness of solution of the system of equations that the model comprises were ascertained. The basic reproduction number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Optimal control is a method used to find the optimal way to control the dynamics of the diseasespreading system via a mathematical approach [8][9][10]. Several studies which have implemented optimal control of the cholera model can be found in [11][12][13][14][15][16][17][18][19][20]. The complex problem for analyzing cholera outbreaks discussing stochastic model, age-structured cholera transmission, and choleraschistosomiasis coinfection can be observed in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal control is a method used to find the optimal way to control the dynamics of the diseasespreading system via a mathematical approach [8][9][10]. Several studies which have implemented optimal control of the cholera model can be found in [11][12][13][14][15][16][17][18][19][20]. The complex problem for analyzing cholera outbreaks discussing stochastic model, age-structured cholera transmission, and choleraschistosomiasis coinfection can be observed in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%